1997
DOI: 10.1109/28.568015
|View full text |Cite
|
Sign up to set email alerts
|

Control topology options for single-phase UPS inverters

Abstract: Abstract-Four control topologies for single-phase uninterruptible power system (UPS) inverters are presented and compared, with the common objective of providing a dynamically stiff, low total harmonic distortion (THD), sinusoidal output voltage. Full-state feedback, full-state command controllers are shown, utilizing both filter inductor current and filter capacitor current feedback to augment output voltage control. All controllers presented include output voltage decoupling in a manner analogous to "back-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(118 citation statements)
references
References 16 publications
0
108
0
10
Order By: Relevance
“…Em geral na malha de corrente utilizam-se controladores do tipo Proporcional (P) (LOH et al, 2003), (ABDEL-RAHIM;QUAICOE, 1996), LAWSON, 1987), (RYAN; BRUMSICKLE; LORENZ, 1997), (SILVA, 1999). justificam o emprego deste tipo de controle num sistema com duas malhas em cascata para controle de uma UPS trifásica, relatando que erros de estado estacionário nesta malha não afetam o desempenho da malha mais externa.…”
Section: Lista De Abreviaturasunclassified
“…Em geral na malha de corrente utilizam-se controladores do tipo Proporcional (P) (LOH et al, 2003), (ABDEL-RAHIM;QUAICOE, 1996), LAWSON, 1987), (RYAN; BRUMSICKLE; LORENZ, 1997), (SILVA, 1999). justificam o emprego deste tipo de controle num sistema com duas malhas em cascata para controle de uma UPS trifásica, relatando que erros de estado estacionário nesta malha não afetam o desempenho da malha mais externa.…”
Section: Lista De Abreviaturasunclassified
“…The simulation circuit is consists of three phase source, controlled rectifier, inverter, SPWM controller, filter, multilevel inner loop controller [9], [10], [11] and three phase nonlinear load. The simulation is done by Matlab /Simulink environment.…”
Section: Simulationmentioning
confidence: 99%
“…The dual-loop control for the single-phase UPS inverter includes an outer voltage loop which regulates the output voltage and ensures zero steady-state error and stability over a wide range of operating conditions and an inner current control loop which compensates the load disturbances and actively damps the possible resonances. It is shown that regardless of the controller type, in dual-loop techniques, the capacitor current feedback brings better disturbance rejection capability than the inductor current feedback [18,19]. This paper proposes a simple dual-loop controller for the single-phase UPS inverter with an LC filter.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent series resistance (ESR) of the filter capacitor is ignored, since it is usually such small that the break frequency becomes much higher than the range of concern. Assuming that the switching frequency is far above the fundamental frequency, Fig As aforementioned, in all dual-loop control schemes suggested for the single-phase UPS inverters, the inner and outer loops are used for current and voltage control, respectively [4,8,[16][17][18][19][20][21][22][23][24]. While these techniques exhibit an acceptable performance, the design of the feedback control loops is complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation